An overlooked modernist: Luis Lacasa - Zarza, Daniel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
The aim of this text is to vindicate the figure of Luis Lacasa as an example of those architects that our particular history has overlooked, possibly because of his consequent decision to go into exile. He was a prestigious architect, demonstrated by some of his notable projects: the Hospital and the Physics Institute in Toledo (with Sánchez Arcas) or his projects for the University Campus in Madrid (dormitories and sports grounds). After the University project he was formally asked to build the Spanish pavilion in Paris (1937), a project that he finally built with Jose Luis Sert. In spite of all that, his professional development in Madrid, Moscow and Pekin declined slowly through the subsequent years. Not even in the Urban Planning Institute of the USSR Architecture Academy did he manage to obtain better assignments than the translation of professional journals. His proven talent to analyze architecture and urbanism was unfortunately wasted. However, Lacasa left to us an important legacy: a realistic concern about some key issues like economical social housing, extensive development and regulation of the building activity, new programs to meet new needs... His ideas concerning dwelling units, slabs, university facilities, leisure spaces for the masses, theatres, cinemas, factories, hospitals, green areas, etc., seem avant-garde to us even now in the field of landscape architecture.